1998
DOI: 10.1525/jlin.1998.8.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Situational Meanings of Japanese Social Deixis: The Mixed Use of the Masu and Plain Forms

Abstract: This article explores indexical relations between honorific forms and their situational meanings by examining the Japanese addressee honorific masu form and its nonhonorific counterpart, the plain form. Arguing against a simple view of these forms as speech‐level markers, the article proposes that both addressee‐deference and speaker‐focused self‐presentation are indexical values of the masu form; the plain form is associated with an absence of these values. By examining two contrastive social situations, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 25 publications
0
50
0
Order By: Relevance
“…Furthermore, it was also demonstrated that honorifics/RF are not always used to show politeness and have other discourse functions, cf. Cook (1998;. Section three tries to corroborate these critiques, from the perspective of historical Chinese politeness.…”
Section: The Objectives and Framework Of The Present Studymentioning
confidence: 86%
“…Furthermore, it was also demonstrated that honorifics/RF are not always used to show politeness and have other discourse functions, cf. Cook (1998;. Section three tries to corroborate these critiques, from the perspective of historical Chinese politeness.…”
Section: The Objectives and Framework Of The Present Studymentioning
confidence: 86%
“…Users' variable evaluations of these categories, the negotiation of identities, positions and stances enacted in situated contexts were put under the spotlight. Politeness theory of this kind (Watts 1989(Watts , 1992Watts et al 1992;Eelen 2001), opened up new avenues of investigation such as the discursive nature of politeness (Watts above and 2003;Locher 2004Locher , 2006Locher , 2008Watts 2005, 2008;Mills 2011) and the strategic nature of honorific usage (Pizziconi 2003;Cook 1998Cook , 2013, the pro-social character of polite behaviour (Sifianou 1992) as well as deliberately confrontational impolite behaviour (Culpeper 1996(Culpeper , 2011Culpeper, Bousfield and Wichmann 2003;Locher and Bousfield 2008;Bousfield , 2010. These trends also showed many synergies and the contributions of different disciplinary traditions, from theories of identity to social cognition, conversation analysis, interactional sociolinguistics, and others (see Locher 2012 for a review).…”
Section: Setting the Research Interfacementioning
confidence: 99%
“…Traditionally it was claimed that the application, unequal use and omission of honorific patterns indicates status differences in Japanese society (Kabaya, 2007). However, discursive studies of speech-level shifts in various contexts, including broadcast interviews, student discussions, and classroom interactions, demonstrated the weakness of this conventional belief (e.g., Cook, 1999;Ikuta, 1983;Usami, 2002). These linguistic studies show that the mixing of honorific and non-honorific language does not directly reflect contextual factors, such as hierarchical difference or level of intimacy, between the interactants.…”
Section: Japanese Honorificsmentioning
confidence: 99%
“…they may omit honorifics in order to create a casual atmosphere (Okamoto, 1999). Thus, speech-level shifts can be observed when speakers change their footing, or adjust psychological distance (Hidaka and Ito, 2007;Cook, 1999;Reisei, 2006: 96-106).…”
Section: Japanese Honorificsmentioning
confidence: 99%